2014
DOI: 10.1111/pin.12175
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD20 expression and Epstein‐Barr virus (EBV) association in classical Hodgkin lymphoma in Japan: A clinicopathologic study

Abstract: To investigate the clinicopathological significance of CD20 expression and Epstein‐Barr virus (EBV) association in Hodgkin and Reed–Sterberg cells of classical Hodgkin lymphoma (CHL), CD20 expression and EBV positivity (by EBER in situ hybridization) were investigated in 389 CHL patients in Japan. They included 74 CD20‐positive cases (19%) and 315 CD20‐negative cases (81%). CD20‐positive cases showed significantly older age at onset (P = 0.018) and higher association with EBV (P = 0.002). Multivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
2
10
1
Order By: Relevance
“…In CHL, there are several poor prognostic factors, including CTM expression, 8 EBV infection, 9 and marked infiltration of CD68-positive macrophages, 10 which were all observed in the current case. In addition, the reasons for the fulminant clinical course in the current case were likely associated with the severe angiodestruction revealed by autopsy.…”
Section: Discussionsupporting
confidence: 60%
“…In CHL, there are several poor prognostic factors, including CTM expression, 8 EBV infection, 9 and marked infiltration of CD68-positive macrophages, 10 which were all observed in the current case. In addition, the reasons for the fulminant clinical course in the current case were likely associated with the severe angiodestruction revealed by autopsy.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, older patients were reported to have a higher proportion of CD20-positivity than younger patients. 18 , 26 - 29 As our study found no significant correlation between CD79a and CD20 expression, they may be independent B-cell markers in CHL. Indeed, CD20- and CD79a-positivity were reported to be only weakly correlated.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast to CD79a, the prognostic impact of CD20 has been well documented, although controversies remain. 26 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, the prognostic relevance of BCA, p53, and Bcl2 in cHL is highly controversial. Literature data on BCA are focused mainly on CD20 and correlate its expression to either worse, 40 neutral, 41,42 or better 43 survival rates compared with controls. The same holds true for Bcl2 and p53, which have been variably associated with prognosis 10,20,43‐49 .…”
Section: Discussionmentioning
confidence: 99%